If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+9-3(x+1)=7x+9
We move all terms to the left:
6x+9-3(x+1)-(7x+9)=0
We multiply parentheses
6x-3x-(7x+9)-3+9=0
We get rid of parentheses
6x-3x-7x-9-3+9=0
We add all the numbers together, and all the variables
-4x-3=0
We move all terms containing x to the left, all other terms to the right
-4x=3
x=3/-4
x=-3/4
| 14.91+0.06x=15.66-0.07x | | 3x+1.4=5.3 | | 3/5x+4/7=-2/9x+4/27 | | 6w-2=9w-14 | | -3.2-(x+19.1)=14.2 | | 90=6(u-75) | | 5=1/2+b | | 8k+-1k=14 | | 4/5(x)+3=43 | | 83=11+9f | | k/3+4-2k=-9k | | 145÷5=(x+8)÷5 | | 5x+35=40+18x-162 | | 14-2k=10 | | 7(k+1)=35 | | (2x+3)/4=3/5 | | 4x+3.9=9.1 | | 3n-16=27 | | -6x+18=-60 | | 13-v/4=15 | | D/3+5x=18 | | 3x-7=x-25 | | (5n+2)/2=11 | | 21-4y=9 | | -11x+5=18 | | 17+6f=41 | | 10y-3y-3=18 | | (86+x)/2=90 | | x(3x-1)^2=0 | | 5x2=28x+12 | | -(x+2)(x-5)(x-3)(x+3)=0 | | 9+2r=15 |